Strengthening Women's Educational Rights Through Majelis Taklim And Its Impact On Social Dynamics In Indonesia - A'thoina, Inna (PT. Student Rihlah Indonesia, 2025)
This study aims to examine the implementation of women's educational rights, particularly in the context of religious education, through non-formal educational institutions such as Majelis Taklim and its impact on society in Indonesia. The research uses a qualitative method with a descriptive-analytical approach and applies triangulation techniques, involving the comparison of data from various sources, including observation, interviews, and documentation. The study was conducted at two Majelis Taklim: Majelis Taklim Al-Ukhuwah in Depok, West Java, and Majelis Taklim Ainul Yaqin in Cilegon, Banten. The findings reveal that Majelis Taklim, as a non-formal educational institution, contributes significantly to supporting the fulfillment of women's educational rights. This contribution is not limited to religious education but also includes broader areas of knowledge, such as psychology, life skills, and social activities.